Dynamics of maternal lymphocyte subsets from 3rd trimester to postpartum and their impact on mother-to-child HIV-1 transmission - Chitsulo, Chimwemwe (My University, 2010)
Background Mother-to-child transmission of HIV infection is the primary cause of paediatric HIV infections worldwide. High HIV infection rates in women of childbearing age (15-49 years) and efficiency of PMTCT have resulted in the high rate of HIV incidence and prevalence in children of sub-Saharan Africa. The stark contrast in the success of PMTCT interventions between the western countries and less developed countries indicates the need for further research to develop alternative, easier, and more effective population-based interventions. Methodology This was a retrospective cohort study of the medical records of approximately 300 HIV infected women enrolled in the Nevirapine Resistance study between May 2002 and February 2003. An assessment of the significance of changes in immunological parameters (CD4 counts, CD4 percentages, CD4/CD8 ratios) and HIV RNA from 3rd trimester to 6 weeks postpartum and causal associations vi between these changes and increased risk of PMTCT was then conducted using logistic regression models. Results Mothers with CD4 counts above 200cells/μL were approximately exhibited onethird the likelihood of transmitting HIV-1 to their infants than mothers with CD4 counts below 200 cells/μL [OR 0.35 (0.13, 0.95)]. High maternal HIV RNA levels demonstrated a stronger association with increased risk of PMTCT with women with postpartum viral loads greater than 100 000 copies/μL exhibiting ten times the likelihood [OR 10.15 (2.17-47.55)]. Statistically significant mean increases in CD4 and CD8 cell counts from 3rd trimester to postpartum were observed. Mean increases in CD4 and CD8 counts demonstrated no association with PMTCT. Conclusion CD4 cell counts and CD8 cell counts underwent statistically significant changes from 3rd trimester to postpartum. These changes seem not to represent any clinically significant change in maternal disease progression during this time period and were found not to be associated with PMTCT.
MSc (Med), Faculty of Health Sciences, University ofthe Witwatersrand, 2007
Keywords: HIV-1; mother to child transmission